Perception as an Integral Reflection - Hovhannisyan, Hrachya (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
So far, there has been no reasonable psychological definition or an explanation of the content of the term “experience”. All existing characteristics or descriptions lead to the explanation most likely of habits, skills or memory. This work is another attempt to theoretically observe human inner as а product of the integration of external and internal impulses respectively mental states. For the explanation of these relations, a descriptive model of integrally triple platform is offered. The axis in this model is a person’s ability to feel. In addition, examples of psychological analysis based on the application of this model are given.
Keywords: integrally triple platform, forms of perception, reflection, domain of mental states, personal state